Safety of Repeated Injections of Sodium Hyaluronate (SUPARTZ) for Knee Osteoarthritis: A Systematic Review and Meta-Analysis. (October 2016) - Bannuru, Raveendhara R.; Brodie, Christopher R.; Sullivan, Matthew C.; McAlindon, Timothy E.
Objective: Though there is no consensus on its efficacy, knee osteoarthritis is symptomatically managed with intra-articular hyaluronic acid (IAHA). Recent reports suggest that IAHA may delay the need for total knee replacement, with the magnitude of delay proportional to the number of injection series. However, the safety of repeated injection series is reported to vary between commercial products. This report describes a systematic review of safety data on repeated treatment courses of SUPARTZ. Design: We performed a systematic search of MEDLINE, Cochrane database, EMBASE, Web of Science, Google Scholar, and unpublished data. We included all human randomized controlled trials or observational studies with adverse event (AE) data for SUPARTZ in knee osteoarthritis. Two independent reviewers extracted data and evaluated study quality. Data were analyzed separately for the first and subsequent series of injections. Results: The primary sources for repeated-injection data on SUPARTZ were a postmarket registry ( N = 7404), 4 prospective studies ( N = 127 total), and a retrospective study ( N = 220). None of the sources reported increased frequency or severity of AEs with repeated injections. In the registry, 95% of multiple-injection-series patients who reported an AE did so during the first series. None of the AEs was serious, and most resolved spontaneously without medical intervention. The overall adverse event rate after repeat courses of SUPARTZ was 0.008 (95% confidence interval: 0.001-0.055). Conclusions: Multiple courses of SUPARTZ injections appear to be at least as safe, and probably safer, than the first course. This study supports the safety of repeat courses of SUPARTZ injections for knee osteoarthritis.